Leadership and Funding: Changes Ahead for Agricultural Safety and Health. Issue 1 (2nd January 2018) - Murphy, Dennis J.; Lee, Barbara C.
ABSTRACT: For the last several decades, financial support for agricultural safety and health programs and professionals has primarily been covered by public dollars through federal and state government grant programs and appropriations. This federal and state funding provided a tremendous boost to farm safety and health professionals and program efforts for 30+ years and has provided the foundation and structure for current agricultural safety and health efforts and activities. However, there is reason to question long-term sustainability of a sufficient level of federal and state dollars for agricultural safety and health. Public funding for agricultural safety and health has never quite kept up to inflation, but even more ominous is that the entire agricultural safety and health program has been proposed for elimination each year by the White House budget beginning with the fiscal year 2012. It seems prudent, perhaps even imperative, for the agricultural safety and health community to find alternative support mechanisms. We suggest that now is a great time for agricultural businesses, services, and organizations to step up their financial support. Fortunately, several positive examples have recently surfaced within the agricultural community. As the agricultural industry continues to be a dominant enterprise in the United States, the integration of significant funding and the role of leadership from within the industry must continue to expand.